DIMENSI KEADILAN GENDER DALAM POLIGAMI: ANALISIS ATAS UNDANG-UNDANG PERKAWINAN DI INDONESIA - Ridwan Ridwan (Yinyang: Jurnal Studi Islam Gender dan Anak, 2011)
Abstract: The practice of polygamy when viewed from a historical perspective of social theology appears that polygamy is an act that is based on social motives, namely to help widows and orphans. Therefore, polygamy should be understood not only as the legalization of gratification of sexual appetite of a man without looking at the dimensions contained spirits (maqhasihd al-shari’a) of the permissibility of polygamy. Although not explicitly, marriage law in force inIndonesia adopts direct text of the Quran and al-Hadith, but the spirit of protection of women (wives) by tightening the terma of the spirit appears to exist for administrative practices mengelmir polygamy. Keywords: Polygamy, Gender equality.